Brief Report: Vascular Dysfunction and Monocyte Activation Among Women With HIV. (1st October 2020) - Toribio, Mabel; Awadalla, Magid; Cetlin, Madeline; Fulda, Evelynne S.; Stanley, Takara L.; Drobni, Zsofia D.; Szczepaniak, Lidia S.; Nelson, Michael D.; Jerosch-Herold, Michael; Burdo, Tricia H.; Neilan, Tomas G.; Zanni, Markella V.
Abstract : Objective: Women with HIV (WHIV) on antiretroviral therapy (ART) face an increased risk of cardiovascular disease (CVD) in the context of heightened systemic immune activation. Aortic stiffness, a measure of vascular dysfunction and a robust predictor of CVD outcomes, is highly influenced by immune activation. We compared aortic stiffness among women with and without HIV and examined interrelationships between aortic stiffness and key indices of systemic immune activation. Methods: Twenty WHIV on ART and 14 women without HIV group-matched on age and body mass index (BMI) were prospectively recruited and underwent cardiovascular magnetic resonance imaging, as well as metabolic and immune phenotyping. Results: Age and BMI did not differ significantly across groups (age: 52 ± 4 vs. 53 ± 6 years; BMI: 32 ± 7 vs. 32 ± 7 kg/m 2 ). Aortic pulse wave velocity (aPWV) was higher among WHIV (8.6 ± 1.3 vs. 6.5 ± 1.3 m/s, P < 0.0001), reflecting increased aortic stiffness. Among the whole group and among WHIV, aPWV related to sCD163 levels (whole group: R = 0.65, P < 0.0001; WHIV: R = 0.73, P = 0.0003) and to myocardial fibrosis (extracellular volume; whole group: R = 0.54, P = 0.001; WHIV: R = 0.47, P = 0.04). Both HIV status and sCD163 levels independently predicted aPWV, controlling for age, BMI, cigarette smoking status, and systolic blood pressure (HIV status: β-estimate = 0.69, 95% CI [0.1 to 1.3], P = 0.02; sCD163: β-estimate = 0.002, 95% CI [0.0006 to 0.004], P = 0.01). Among WHIV, sCD163 levels independently predicted aPWV, controlling for duration of HIV, CD4 count, and HIV viral load (sCD163: β-estimate = 0.004, 95% CI [0.002 to 0.005], P = 0.0005). Conclusions: Asymptomatic WHIV on ART have increased aortic stiffness as compared to matched control subjects. Among WHIV, aPWV related to heightened monocyte activation (sCD163) and to downstream CVD pathology (myocardial fibrosis). ClinicalTrials.gov Registration: NCT02874703. Abstract : Supplemental Digital Content is Available in the Text.